#WMHD Talks: Analyses of Mental Health Conversations Among Indonesian Community on Twitter - Muhiddin, Syurawasti; Wodong, Griselda Maria Ancela; Yudistikhar, Afga; Idham, Azmul Fuady; Vanessa, Audrey Alya; Soharto, Patricia Cecilia (Faculty of Psychology, Universitas Gadjah Mada, 2024)
One of the right moments to comprehend people’s understanding of mental health topics is through World Mental Health Day (WMHD). This study aimed to explore themes related to mental health that are the conversation topics on Twitter as social reactions to WMHD 2021. We collected and analyzed Indonesian tweets that contained #WMHD or Mental Health keywords. From October 1 to 23, 2021, a total of 12,500 tweets were collected utilizing tweepy and request, a python programming-based library. Data cleaning processes left 7,126 tweets to be further analyzed with inductive thematic analysis. This study found seven themes from the most to the least frequently discussed, namely (1) positive mental health, (2) social network and social capital, (3) mental health literacy, (4) stressful events, (5) material economic well-being, (6) mental illness and (7) physical wellbeing. This research showed that social media has the capacity to investigate users’ knowledge and perception which might then serve as the foundation for providing relevant mental health education on various platforms to support the improvement of community well-being. Furthermore, knowing the topics of mental health-related conversations on twitter can be a precursor to the development of a measurement tool related to mental health understanding.